Involvement of Students With Severe Disabilities in Specialized Health Care Procedures. (October 2019) - Ballard, Sarah L.; Dymond, Stacy K.
A recommended practice in the field of severe disabilities is involving students in their specialized health care procedures; however, little is known about how this practice is occurring in schools. The purpose of this qualitative multiple-case study was to understand how secondary-age students with severe disabilities are involved in their specialized health care at school. Purposeful sampling resulted in nine cases and a total of 41 participants. A case comprised a secondary-age focus student and the student's parent(s), special education teacher, school nurse, and classroom nurse or paraprofessional. Data sources were observations, interviews, and document reviews. The researchers analyzed the data using an iterative inductive coding approach for each individual case to identify patterns in the data followed by a cross-case synthesis using visual matrices to identify salient themes across cases. This process resulted in four themes depicting how students were involved in their specialized health care at school, which were (a) partially participating, (b) interacting with adults, (c) engaging in risky behaviors, and (d) passively participating. The findings from this study highlight a need for improved attention to the promotion of self-care in specialized health care for this population.